2018
DOI: 10.17705/1atrr.00023
|View full text |Cite
|
Sign up to set email alerts
|

Training, Self-Efficacy, and Performance; a Replication Study

Abstract: Abstract:A conceptual replication of multiple prior IS studies was conducted with the aim of providing stronger empirical support for those results. Conducting six separate longitudinal studies, the effect of professional training on improving one's application-specific computer self-efficacy (AS-CSE) was shown. Also in line with some prior IS studies it was shown that an application-specific measure of self-efficacy is better able to predict one's performance in accomplishing tasks in the corresponding domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Further, workshops on learning skills also increase people's self-efficacy (Rachmawati, 2008). Additionally, professional training has been confirmed to enhance an individual's self-efficacy (Davazdahemami, Luse, Scheibe, & Townsend, 2018). Therefore, an individual's self-efficacy is significantly affected by workshops and training to advance their personal performance (Zaki, Ali, Bakar, & Sarwar, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Further, workshops on learning skills also increase people's self-efficacy (Rachmawati, 2008). Additionally, professional training has been confirmed to enhance an individual's self-efficacy (Davazdahemami, Luse, Scheibe, & Townsend, 2018). Therefore, an individual's self-efficacy is significantly affected by workshops and training to advance their personal performance (Zaki, Ali, Bakar, & Sarwar, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the relationship between self-efficacy and performance in an industrial context. This relationship already was investigated in academic setting [11] in Software Engineering and is critical.…”
Section: Discussionmentioning
confidence: 99%
“…The items were the same at both time periods and adapted from guidelines set forth by previous research (Marakas et al, 2007) who suggested that task-specific measures of self-efficacy offer greater insight into individual self-efficacy assessment due to the context-specific nature of the questions. These specific task-specific self-efficacy question in relation to computer networking set-up were used in previous research to help validate the use of task-specific measures of self-efficacy (Davazdahemami et al, 2018). See the Appendix for the specific questions used.…”
Section: Study Design Materials and Methodsmentioning
confidence: 99%
“…Constructs for measuring self-efficacy are now developed within each specific domain of interest (Agarwal et al, 2000;Johnson & Marakas, 2000;Marakas et al, 2007). Since the authors' work was in a networking course, selfefficacy questions focus on network concepts and skills gained from the weekly labs, as well as the 'corporate' network final project as previous work shows necessary (Davazdahemami et al, 2018;Luse et al, 2014). Given the above, we hypothesise, Hypothesis 2 Weekly skills-mastery labs utilising the novel ISEAGE Internet testbed will positively increase student self-efficacy with regard to networking and infrastructure.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation